Respuesta :

Answer: Second Option

[tex]f (x)=\frac{2}{x}[/tex] and [tex]g(x)=\frac{2}{x}[/tex]

Step-by-step explanation:

If we have a function f(x) and its inverse function [tex]f ^ {- 1} (x) = g (x)[/tex]

Then by definition:

[tex](fog) (x) = (gof) (x) = x[/tex]

Notice that the inverse of the function [tex]f (x)=\frac{2}{x}[/tex] is [tex]f ^ {- 1}(x)=\frac{2}{x}[/tex]

then:

If [tex]f (x)=\frac{2}{x}[/tex] and [tex]g(x)=\frac{2}{x}[/tex]

Then:

[tex](fog) (x) =\frac{2}{\frac{2}{x}}[/tex]

[tex](fog) (x) =\frac{2x}{2}[/tex]

[tex](fog) (x) =x[/tex]

The answer is the second option

ACCESS MORE